2017
DOI: 10.1111/jabr.12105
|View full text |Cite
|
Sign up to set email alerts
|

Somatization disorder and stress in teachers: a comprehensive occupational health evaluation

Abstract: Somatization disorder is a biopsychosocial‐based, stress‐induced disorder involving multiple physical ailments with no medical explanation. The teaching profession is characterized as very stressful, making teachers at risk of developing somatization disorder. This study examined somatization disorder in a K‐12 teacher population. A total of 2,988 teachers from 46 Texas districts responded to a comprehensive online occupational health survey. Somatization disorder was assessed using the Patient Health Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Another individual difference is psychological strain. Previous research also shows that teachers often experience psychological strain, which is associated with their attitude towards students with ADHD [31,32]. More precisely, psychological strain is linked to a weaker intention in pre-service teachers to implement effective CMS [20].…”
Section: Individual Differencesmentioning
confidence: 97%
“…Another individual difference is psychological strain. Previous research also shows that teachers often experience psychological strain, which is associated with their attitude towards students with ADHD [31,32]. More precisely, psychological strain is linked to a weaker intention in pre-service teachers to implement effective CMS [20].…”
Section: Individual Differencesmentioning
confidence: 97%
“…These findings resonate with the notion that depression, anxiety, and somatization are the most prevalent mental health disorders observed among the general population in primary care, presenting substantial challenges for the health care system in terms of detection and treatment in general (Hanel et al, 2009) and during COVID-19 in particular (Ran et al, 2020; Shangguan et al, 2020). In particular, prior research has demonstrated that over 30% of public school teachers met the criteria for somatic disorder (Howard et al, 2017). Being a stress-induced disorder, somatization has been associated with the excessive occupational stress inherent in the teaching profession, as well as with elevated levels of anxiety and depression and prospective professional burnout among teachers (Gillet et al, 2022; Howard et al, 2017).…”
Section: The Implications Of Covid-19 On Teaching Staffmentioning
confidence: 99%
“…31 Howard et al contended that MH disorders can be caused by various circumstances, such as work stress, which is often encountered by teachers. 32 Kidger et al found low wellbeing experienced by teachers to be the result of stressful workloads, dissatisfaction with coworkers’ performance, and the inability to convey feelings and concerns to others, which can elicit moderate to high symptoms of depression. 33 …”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%